FOSTERING VOCABULARY MASTERY THROUGH AN AUDIO TEXTBOOK AT THE SEVENTH GRADER OF SMP NEGERI 7 TARAKAN - Gela, Friska Angelika; Ramli, Ramli; Eppendi, Jhoni (Universitas Borneo Tarakan, 2023)
The lexicon of a language is a crucial part of its linguistic structure. If students lack a thorough comprehension of vocabulary, their proficiency in English will be adversely affected. However, students should prioritise improving their ability to regulate and use words. This study aimed to determine if there is a distinction in vocabulary proficiency among seventh-grade students at SMP Negeri 7 Tarakan when taught using audio textbooks as a learning medium compared to traditional media. The research findings indicate that students who received instruction using audio textbooks had a significant disparity in their vocabulary proficiency compared to those taught using conventional textbooks. Consequently, listening to audiobooks might prove advantageous for students in enhancing their language proficiency. Teachers at SMP Negeri 7 Tarakan and other schools are contemplating using diverse technological media, such as audio textbooks, to aid pupils in acquiring language skills. This is being undertaken in an attempt to build innovative teaching approaches.Â